2008 30th Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2008
DOI: 10.1109/iembs.2008.4649234
|View full text |Cite
|
Sign up to set email alerts
|

A brain-computer interface (BCI) system based on auditory stream segregation

Abstract: An auditory brain-computer interface (BCI) which detected event-related potential (ERP) elicited by selective attention to one of the tone streams was proposed. Each tone in two kinds of frequency oddball tone sequences with different tone frequency range was presented alternatively to subjects, and they were perceived by subjects as two kinds of segregated streams. Event-related potentials elicited by two kinds of deviant tones were classified by linear discriminant analysis (LDA) to find which streams subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 4 publications
(2 reference statements)
1
22
0
Order By: Relevance
“…To overcome the limitations of conventional BCI paradigms, some researchers have turned to auditory stimuli (Hill et al, 2005;Kanoh et al, 2008;Lopez et al, 2009;Klobassa et al, 2009;Schreuder et al, 2010) as an alternative to visual stimuli. Most of the previous studies used auditory oddball paradigms, which share most of the basic concepts with conventional visual BCI paradigms.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To overcome the limitations of conventional BCI paradigms, some researchers have turned to auditory stimuli (Hill et al, 2005;Kanoh et al, 2008;Lopez et al, 2009;Klobassa et al, 2009;Schreuder et al, 2010) as an alternative to visual stimuli. Most of the previous studies used auditory oddball paradigms, which share most of the basic concepts with conventional visual BCI paradigms.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the previous studies used auditory oddball paradigms, which share most of the basic concepts with conventional visual BCI paradigms. Two of the earliest studies (Hill et al, 2005;Kanoh et al, 2008) independently introduced an auditory BCI paradigm in which the authors attempted to discriminate "attended" brain responses from "unattended" ones when two simultaneous auditory oddball streams were presented to subjects. In a study by Hill et al (2005), deviant sounds were generated alternatively at either a right or left sound source, and subjects were asked to concentrate on one of the two sound sources.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To this regard, Murguialday and colleagues [15] have recently reported on a patient in a completely locked-in state due to a progressive neurodegenerative disease (amyotrophic lateral sclerosis) who had lost all afferent pathways except for the auditory system. Previous findings have already highlighted the suitability of an auditory paradigm based on the stream tone segregation phenomenon in the BCI framework [16], [17]. These studies showed promising results but exclusively in healthy participants.…”
Section: Approachmentioning
confidence: 86%
“…Longer breaks were taken between the runs according to the patient's needs. After the simple paradigm, a complex paradigm based on the auditory stream segregation phenomenon [17] was used. Both, the LTS and HTS, were intermixed (with 150 ms offset) and simultaneously presented to the patient resulting in a stream pattern of LHL LHL .…”
Section: B Paradigm Descriptionmentioning
confidence: 99%